Sejarah Pemikiran Ekonomi Islam di Masa Rasulullah Saw. - Winarno, Winarno (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2017)
Rasulallah Saw. was sent to the earth was carrying the mission that Allah is the almighty and take the mandate to build human civilization more dignified than ever. One form of construction was built by Rasulallah Saw. In order to create a dignified human being from the aspect of the economy. The economic aspect is a form of a right economy that is, protected from things prohibited by syara 'such as manipulation, fraud, corruption and so forth.The history records that, the beginning of Islamic economic thought has actually been done by Rasulallah Saw. and his companions (khulafaurasyidin). The economic problems of the people become very serious concerns because economic problems are the pillars of the faith that must be considered. This is as narrated by Muslims, that Rasulallah Saw. Says "Poverty leads people to disbelief". So the effort to eradicate poverty is part of the social policies undertaken by him at that time. Rasulallah Saw. laid the foundations of the state's financial system in accordance with the provisions of the Qur'an. The whole paradigm of thinking in the economic field and its application in everyday life that was inconsistent with Islamic teachings was removed and replaced with a new paradigm that conforms to Qur'anic values, namely brotherhood, equality, freedom and justice. So this was a very significant step, as well as brilliant and spectacular at the time.